Effect of Sodium Valproate pretreatment on Apomorphine and Dexamphetamine induced Stereotyped Behavior in rats. - Sattigeri, B M; Balsara, J J; Jadhav, J H; Sattigeri, M M; Bhatt, Astha (Recent Research in Science and Technology, 2012)
Sodium valproate a broad spectrum antiepileptic elevates the brain GABA levels. Studies have suggested regulatory role of GABA on dopaminergic neurons, which is evident by behavioral studies in animals that reveal functional interaction between GABAergic and DAergic systems. Hyperfunctioning of DAergic system in rats is responsible for occurrence of stereotyped behavior (SB) in them. Drugs like apomorphine (Apo) and amphetamine induce SB by acting directly or indirectly. GABA, by acting at different sites has shown to influence the dopaminergically mediated behaviors. Hence the study was taken up to investigate the effect of sodium valproate pretreatment on apomorphine and dexamphetamine induced SB in rats. Pretreatment with 100 to 400mg/kg sodium valproate did not antagonize the apomorphine induced SB, however pretreatment with 100 to 400mg/kg sodium valproate significantly antagonized SB induced by 10 & 15mg/kg dexamphetamine.